2018
DOI: 10.29333/ejac/85009
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Nurses’ Moral Sensitivity and Patients’ Satisfaction with the Quality of Nursing Care

Abstract: Patient satisfaction is considered as an important indicator of the quality and effectiveness of health system. Moral sensitivity plays an important role in how professional responsibilities and moral decisions are made by nurses. This study aims to investigate the relationship between nurses' moral sensitivity and patients' satisfaction with quality of nursing care. This study is descriptive and analytic. First, nurses in internal, surgical and special wards were selected through census method. Then, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In this regard, we believe, as do other authors [3,4], that a lack of moral sensitivity in clinical practice could place the quality of professional healthcare performance at risk. Logically, high-quality clinical practice requires not only technical training and command of technological advances, but also congruent moral reasoning based on their own moral principles to guide them in their professional performance [5,6].…”
Section: Moral Sensitivity In Nursing Practicementioning
confidence: 70%
“…In this regard, we believe, as do other authors [3,4], that a lack of moral sensitivity in clinical practice could place the quality of professional healthcare performance at risk. Logically, high-quality clinical practice requires not only technical training and command of technological advances, but also congruent moral reasoning based on their own moral principles to guide them in their professional performance [5,6].…”
Section: Moral Sensitivity In Nursing Practicementioning
confidence: 70%
“…HCWs frequently suffer from ethical issues due to difficult working conditions and providing acute or intensive care services, 3,31,32 and consequently, they are exposed to conflict and tension situations intensely. 5,11,33,34 In the study, HCWs with a family member diagnosed with Covid-19 had high ethical sensitivity in terms of the dimension of conflict. The result suggests that dealing with ethical issues encountered in this process increases the awareness and sensitivity of the participants about ethical issues, and this situation reflects positively, especially in the field of conflict.…”
Section: Discussionmentioning
confidence: 91%
“…Also, according to Jiang et al (2021), participants with a higher moral sensitivity score had higher scores on their caring behaviours for COVID‐19 patients in China. The findings of studies performed in other care settings also showed that, with an increase in the moral sensitivity of nurses, patient satisfaction with the nursing care quality (Gholjeh et al, 2015; Shahvali et al, 2018) and care behaviour of nurses (Afrasiabifar et al, 2021; Mert Boğa et al, 2020; Taylan et al, 2021) would also increase. In contrast to the present study findings, the study of Nazari et al (2022) in Iran showed that with an increase in moral sensitivity, the nursing care quality in elderly patients with COVID‐19 decreased (Nazari et al, 2022).…”
Section: Discussionmentioning
confidence: 94%